2015
DOI: 10.1186/s12894-015-0042-5
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic management of asymptomatic and symptomatic simple parapelvic renal cysts

Abstract: BackgroundTo investigate feasibility and safety of treating simple parapelvic renal cysts using flexible ureteroscopy with the Holmium laser.MethodsBetween February 2010 and July 2013, a total of 21 patients, aging from 29 to 71 (49.00 ± 13.23), were diagnosed with parapelvic renal cysts by ultrasonography in combination with contrast-enhanced computer tomography (CT) and intravenous urography (IVU) in the Department of Urology Surgery, People’s Hospital of the Zhejiang province. Fifteen patients were asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Antegrade percutaneous nephroscopic ablation, with cyst wall fulguratation using a resectoscope with a rollerball electrode, has also been demonstrated to be safe and effective [2]. More recently, retrograde management with flexible ureteroscopy and incision and drainage of the renal cyst wall using a holmium laser has been demonstrated to be safe and effective [5]. Ureteroscopy is the least invasive option following simple aspiration; however, it is reserved for smaller cysts and is contraindicated in the presence of ureteric stricture.…”
Section: Discussionmentioning
confidence: 99%
“…Antegrade percutaneous nephroscopic ablation, with cyst wall fulguratation using a resectoscope with a rollerball electrode, has also been demonstrated to be safe and effective [2]. More recently, retrograde management with flexible ureteroscopy and incision and drainage of the renal cyst wall using a holmium laser has been demonstrated to be safe and effective [5]. Ureteroscopy is the least invasive option following simple aspiration; however, it is reserved for smaller cysts and is contraindicated in the presence of ureteric stricture.…”
Section: Discussionmentioning
confidence: 99%
“…In another series with a mean follow-up of 39 months (range 10–72), the radiologic disappearance of the cyst was achieved in 22 (78.6%) of the 28 treated patients; the cyst size reduced to less than half of the previous size in 4 (14.3%) and recurred in 1 [18]. Mao et al [12] reported about 21 patients with RSCs greater than 3 cm treated by RIR-HoLI; however, only 6 were symptomatic. At 15 months follow-up, there was one recurrence requiring laparoscopic treatment; all 6 symptomatic patients became and remained ­asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is highly effective but with a lower risk of complications. In particular, the excellent vision prevents the risk of urinary fistula, which may follow laparoscopic unroofing due to incapacity to distinguish the cyst from the renal collecting system [12]. Finally, laparoscopic unroofing is more expensive and requires more advanced surgical skills than RIR-HoLI [9, 11, 24, 25]; however, it remains appropriate in case of ureteral stenosis or cysts suspicious for malignancy [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parapelvic cyst is a rare disease in the clinic with a detection rate in autopsy of about 1.25-1.5%. 1 It is believed to originate from the secondary lymphatic obstruction, 2 and most of the patients were occasionally found without any symptoms. 3 However, when the cyst is large enough, it may lead to hypertension, haematuria, hydronephrosis or secondary infection, and even acute renal failure.…”
Section: Introductionmentioning
confidence: 99%